Herding with and without Payoff Externalities - An Internet Experiment - Mathias Drehmann; Jörg Oechssler; Andreas Roider (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
Most real world situations which are susceptible to herding are also characterized by direct payoff externalities. Yet, the bulk of the theoretical and experimental literature focuses on pure informational externalities. In this paper we study several different forms of payoff externalities that interact with a standard herding model. More than 6000 subjects, including a subsample of 267 consultants from an international consulting firm, participated in an internet experiment. We also replicate and review earlier cascade experiments. Finally, we study reputation effects in the context of herding.
Keywords: C92; D8; 330; information cascades; herding; network effects; experiment; internet; Anlageverhalten; Test; Internet; Informationsverhalten; Rationales Verhalten; Deutschland